Feminism comes to campus: women at CSU 1960-1971 - Russo, Andrea E., author (Colorado State University. Libraries, 1994)
During the sixties students protested everything from restrictive social regulations to the Vietnam War. In this changing environment women, relying on skills learned in mainstream and protest activities, demanded changes for themselves. By the end of the decade these factors converged to foster the emergence of a feminist consciousness among some CSU women. In addition this thesis examines the important role of male student leaders, who had both a provocative and paternalistic relationship with women, in the development of feminism on campus. Relying upon the student newspaper, the CSU Collegian, oral interviews, and other university materials from that era I demonstrate the importance of the campus to the emergence of feminism in the sixties and early seventies. Chapter One examines the early protests of women and men against restrictive housing regulations and demonstrates that the fights against parietal rules was important for the formation of strategies and tactics that would be used later when feminists explicitly challenged gender-specific forms of university discrimination. Chapter Two explores how local and national events of the mid-sixties influenced women activists at CSU and nurtured a budding feminist consciousness on campus. Chapter Three, through an examination of women's organizations, shows that a feminist consciousness was clearly present on campus by 1968.
Covers not scanned.
Keywords: Colorado State University -- History -- 20th century